The genes associated with gonadotropin-releasing hormone-dependent precocious puberty - Jin Soon Hwang (Korean Pediatric Society, 2012)
Human puberty is a complex, coordinated biological process with multiple levels of regulations. The timing of puberty varies greatly in children and is influenced by both environmental and genetic factors. The key genes of pubertal onset, KISS1, GPR54, GNRH1 and GNRHR, may be major causal factors underlying gonadotropin-releasing hormone-dependent precocious puberty (GDPP). Two gain-of-function mutations in KISS1 and GPR54 have been identified recently as genetic causes of GDPP. GNRH1 and GNRHR are also gene candidates for GDPP; however no mutations have been identified in these genes. Presently potential genetic causes like LIN28B continues to appear; many areas of research await exploration in this context. In this review, I focus primarily on the genetic causes of GDPP.